Coronary heart disease and tuberculosis: an unnoticedsyndemia. Review of literature and management proposal - Murillo Moreno, Mauricio Andrés (2024)
Tuberculosis is a disease that is increasing and affects about 1/3 of the world’s population. In line with the increase in tuberculosis, cardiovascular disease has had a similar behavior to this group, ischemic coronary heart disease has become the main cause of death worldwide. It could be extracted, based on literature, a relationship between tuberculosis and ischemic coronary heart disease through risk factors in common and from a possible pathophysiological substrate that links them. The presentation of these two entities reported so far is varied: it has been found as a debut of an acute coronary syndrome in patients with active tuberculosis, and the progressive development of coronary atherosclerosis in patients with latent tuberculosis, among others. Given this possible link and the progressive increase in its incidence rates, we can affirm that we are facing an inadvertent syndemia, and their management faces a challenge for the great pharmacological interactions. The purpose of this review is to clarify this possible link, propose an approach to diagnosis as well as supply an algorithm for the treatment of the entire spectrum of coronary heart disease that coexists with tuberculosis according to the currently available literature.